Cytomorphological Patterns associated with Lymphadenopathy; A Study of FNACs conducted at A Tertiary Care Public Hospital of Rawalpindi - Hajra Shakil, Muhammad Nauman Tariq2, Ammara Ijaz, Hajra Shakil, Muhammad Nauman Tariq2, Ammara Ijaz (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Lymphadenopathy is an important clinical manifestation of a vast variety of diseases Fine needle aspiration cytology (FNAC) plays an important role in the cytomorphological diagnosis of lymphadenopathy. The present study was undertaken to assess the different cytomorphological patterns associated with lymphadenopathy and to explore the spectrum of lesion with respect to the age and gender. Methods: This descriptive cross sectional study was conducted in the Pathology Department of Benazir Bhutto Hospital, Rawalpindi, from April 2015 to April 2016. All the consecutive 195 FNACs performed during this one year on lymph nodes were included in study. Results: Lymphadenopathies were common among younger patients with the maximum number of incidence in the age group of 11-30 years (53.3 %). The most common finding was Reactive hyperplasia, 112 cases (57.4%), followed by Chronic Granulomatous inflammation with 73 cases (37.4%). There were 3 cases (1.54%) of lymphoproliferative disorders; two Hodgkin’s and one Non-Hodgkin’s lymphoma while 7 cases (3.6%) were diagnosed with metastatic carcinoma. The most common site involved was cervical nodes with 141 (72.3%) cases. Conclusion: Reactive hyperplasia was the most common diagnosis through FNAC in our study followed by chronic granulomatous inflammation.